MINAT MASYARAKAT PADA KESENIAN MELAYU DI KECAMATAN SUNGAI APIT KABUPATEN SIAK - Deni Ariandi; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Public interest in Malay arts in the homeland of Malay namely in Riau Province, to be precise in Sungai Apit District, Siak Regency, is experiencing a decline. Malay art is the culture of the Malay community that has always existed and has made the characteristics of the Malay. This research specifically discusses Malay musical art because Malay music has almost disappeared from the homeland of Malay and I personally don't want Malay music to disappear like Malay Arabic writing, which I had studied when I was a child in school. This study aims to determine the community's interest in Malay arts and to analyze efforts for the preservation of Malay arts in Sungai Apit District. This study uses qualitative techniques using observation, interview, and documentation techniques on all activities in the study. The result of this research is to find out the people's interest in Malay arts which can be concluded that the lack of interest of the people in Sungai Apit District cannot be separated from the increasingly modern times. And there are also efforts made by people from various statuses of society. Key Words: Interests, Malay Arts, Culture